Covid-19 Vaccine and Scholastic Performance of Learners: A Perspective of Internal Stakeholders - Modiba, Ngwako Solomon (International Journal of Criminology and Sociology, 2021)
This paper interrogates the relationship between the availability of the Covid-19 vaccine and the impressive learner results in secondary schools. The paper resulted from diverse discourses, some of which emphasize that the prevalence of Covid-19 in the world has dampened schools' learning moods to the level of flooring learner performance. This paper is conceptual and empirical within the qualitative research paradigm. The question guiding this paper is: to what extent could secondary schools produce inspiring learner results through revelatory information on the availability of vaccination for Covid-19 sufferers? Narrative inquiry and interviewing techniques were used to collect data. Out of the population of 15 secondary schools in one of the circuits in Sekhukhune district in Limpopo Province, South Africa, 3 were conveniently sampled. In each of the 3 sampled secondary schools, only Deputy Chairpersons of the School Governing Bodies and Chairpersons of the Representative Council of Learners became research participants. Findings revealed that underrating the revelatory information of vaccine availability for Covid-19 sufferers was costly for schools. Secondly, failure to consolidate learner solidarity against Covid-19 to improve the quality of schooling life was a problem. Thirdly, the inability by schools to prevent passive teaching and learning through the utilization of the Covid-19 threat. Fourthly, the inability by secondary schools to apply Covid-19 threat to encourage overachievement by learners. Fifthly, inability by schools to push back the frontiers of mediocre performance by applying Covid-19 as a rallying point. Lastly, schools failed to utilize the prevalence of Covid-19 to keep pupils psychologically and developmentally ready for lessons. The researcher recommends applying the ebullient classroom environments to keep teaching and learning memorable, theatrical, and therapeutic, despite the prevalence of the Covid-19 pandemic.